A The Description Of The Ninth Grade Junior High School Students’ Cognitive Ability In Completing The Two Linear Variables Equation Viewed From Solo Taxonomy - Nuringtyas, Sesilia Intan Kusuma; Yunianta, Tri Nova Hasti (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This research is qualitative descriptive research which aims to describe ninth grade students' cognitive abilities in solving the problem of two-variable linear equations (PLDV) through Solo Taxonomy. The techniques of data collection were tests, interviews, and documentation. The credibility of the data in this research is guaranteed using the triangulation method. The results of this research, based on five levels of Solo Taxonomy, show the students' understanding and problem-solving abilities based on their cognitive abilities. In this case, the subject of high cognitive ability (DW) was able to reach five levels of the Solo Taxonomy and the subject of moderate cognitive ability (RN) was able to reach three levels of the Solo Taxonomy. So that it can be said that the two subjects were able to understand and solve the problem of two-variable linear equations (PLDV). The subject of low cognitive ability (AB) was able to reach one level of Solo Taxonomy so that it can be said that the subject has not been able to understand and solve PLDV problems.